Effect of mineral in coal on preparation of activated carbon for methane decomposition to hydrogen. (15th December 2019) - Wang, Yajie; Yang, He; Jin, Lijun; Li, Yang; Hu, Haoquan; Ding, Hua; Bai, Xiangfei
Highlights: Floated coal was used to study the roles of coal mineral in preparation of AC. Higher mineral content makes total surface area decline, but mesopore developed. Mineral composition affects total and mesoporous surface area and pore volume. High Si-, Fe- and Ca- species in mineral are beneficial to mesoporous formation. Excessive minerals in carbon precursor decrease total and mesoporous surface area. Abstract: Coal samples with different content and composition of minerals floated from Xiaoquan coal with different density solution were used as carbon precursor to prepare AC for catalytic methane decomposition (CMD) to hydrogen. The results showed that the mineral content and composition in coal sample have an obvious effect on the textural properties of the resultant AC. With the increase of mineral content in coal, the prepared AC shows a decreasing trend of surface area while the mesoporous surface increases. The washing method after carbonization/activation of coal samples seriously affects the textures of resultant AC. Washing with HCl solution results in the increase of surface area and pore volume of AC despite of its high mineral content, indicating HCl-soluble species play a positive role in the pore formation, especially for mesopores. But excessive minerals in carbon precursor will lead to the decrease of total and mesoporous surface area because the structure of AC can be destroyed after removal of bulk minerals. The mineral compositions in coal also influence total and mesoporous surface area and pore volume. High Si-, Fe- and Ca-containing species in minerals are beneficial to the formation of mesopores during activation, and improve mesoporosity of the obtained ACs. The resultant AC catalysts from coal with different minerals influence the CMD. With increasing the mineral content in coal sample, the prepared catalyst exhibits better stability, which is ascribed to more mesopores. This work is helpful to recognize the mineral role of carbon precursor in preparation of ACs.